Ethnic differences in response to directive vs. non-directive brief intervention for subsyndromal depression. (4th March 2019) - Pan, David; Huey, Stanley J.; Heflin, Lara H.
Abstract: Objective: Analog research suggests that directive interventions might increase treatment engagement for non-symptomatic Asian American (AA) students; however, no studies have assessed whether directiveness improves therapy processes or clinical outcomes for AAs with mental health symptoms. This study tested the comparative efficacy of brief directive vs. non-directive intervention for AAs and European Americans (EAs) with subsyndromal depression. Method: Participants were randomly assigned directive, non-directive, or cultural values interview conditions, and assessed three times over six months. Directive and non-directive treatment involved meeting with a therapist for a single, 20-minute session to receive psychoeducation and personalized feedback on depressive symptoms and coping strategies. Cultural values participants also met with a therapist. Results: Although results were mixed for the overall sample, directive treatment was generally superior to non-directive treatment and cultural values at addressing depressive symptoms, coping behavior, and working alliance. Ethnicity did moderate treatment effects for some outcomes, but in an unexpected manner. At six-month follow-up, the directive intervention was more effective than cultural values at reducing depressive symptoms for AAs; however, the cultural values condition was more effective than the non-directive intervention at reducing depressive symptoms for EAs. Conclusion: Mixed evidence was found for directiveness as an Asian-specific treatment enhancement. Clinical or methodological significance of this article: This article adds to a complicated body of research and clinical work aiming to inform best practices for ethnic minorities. We found some evidence that a directive therapeutic style may be a "culturally invariant" clinical technique that could be beneficial to Asian American and European American populations alike. Yet, other findings suggest that directiveness might be uniquely advantageous for Asian Americans, particularly for long-term improvement of depressive symptoms.